Frames : Viewing Finnish Contemporary Photography. - Elovirta, Arja; Heikka, Elina; Heikko, Elina; Järvinen, Jukka; Kivirinta, Marja-Terttu; Kovalainen, Ritva; Krappala, Mari; Lintonen, Kati; Lohiniva, Leena; Lundström, Jan-Erik; Martikainen, Aino; Partanen, Markus; et al. (Helsinki : FRAME Finnish Fund for Art Exchange, 1998)
Arstila, Tone ; Bremer, Stefan ; Heikkilä, Jaakko ; Helander, Marja ; Jokisalo, Ulla ; Kaila, Jan ; Kapa ; Kekarainen, Pertti ; Kelaranta, Timo ; Kolehmainen, Ola ; Korhonen, Nina ; Kuukka, Raakel ; Laukia, Armi ; Männikkö, Esko ; Parantainen, Jyrki ; Pirilä, Marja ; Puranen, Jorma ; Renvall, Seppo ; Sammallahti, Pentti ; Soinio, Karl ; Tikka, Heidi ; Turunen, Pekka
Engels
boek
Keywords: Finland